Toward strong X-band-electromagnetic-wave-absorbing materials: polyimide/carbon nanotube composite aerogel with radial needle-like porous structure. Issue 47 (4th November 2022) - Liu, Shi; Xu, Qiang; Bai, Yuting; Wang, Xu; Liu, Xiangyang; Yan, Cenqi; Wang, Yinghan; Qin, Jiaqiang; Cheng, Pei
Abstract : Polyimide/carbon nanotube aerogels with radial needle-like porous structures were designed through radial freeze-drying methods, which show excellent thermal stability, mechanical properties, and electromagnetic interference shielding performance. Abstract : Due to high conductivity, lightweight, good corrosion resistance, and designable structure, polymer/carbon aerogels have attracted considerable attention and have become a candidate for a new generation of electromagnetic interference shielding materials. However, caused by the disordered honeycomb micropore, most polymer/carbon aerogels show relatively low absorption shielding effectiveness/total shielding effectiveness (SEA /SET ) at present. This feature will restrict the application of polymer/carbon aerogels in some specific areas, such as stealth aircraft and reconnaissance planes. In this work, a regular microporous structure was designed to address the above issues through radial freeze-drying methods. The fabricated polyimide/carbon nanotube aerogels with radial needle-like porous structure show excellent thermal stability, compressive mechanical properties, and electromagnetic interference shielding performance (∼53.1 dB with a thickness of 2 mm in the axial direction). The SEA /SET value of the polyimide/carbon nanotube aerogels is as high as 94.5%.